A Better Way to Run a Tongue Tie Service: A 10 year Service Evaluation. Issue 1 (January 2022) - Doughty, Faye; Cousin, Gary; Kanoun, Nadia
Abstract : Introduction: The majority of OMFS units do not have a specific referral pathway for tongue ties, with many patients being seen on an ad hoc basis. Data collated from a 10 year service review highlights the service need for designated tongue tie clinics. Specific clinics reduce waiting times and provide a clear referral pathway for healthcare professionals involved in infant feeding. Objectives: To determine main source of tongue tie referrals, reasons for referrals and to assess complication rates. Methods: Data analysis captures 1159 babies who had tongue ties released between 2011 and July 2021 by one surgeon. The following data was analysed: referral source, gender, age, current feed, main problem (reason for referral) and complication rates. Data was stored on a secure NHS hard drive. Results: Average age at release in a one-stop clinic was 44 days, ranging from 1-275 days old. A 3:2 male to female ratio was observed. The most common source of referral was from midwives (31.8%). The main reasons for referral were issues with breastfeeding (74.2%) and bottle feeding (18.3%). Time from referral to procedure was reduced after dedicated clinics were started. There were no serious complications, and a low rate of minor complications. Conclusions: The release of tongue ties is a quick, safe procedure. Waiting times were reduced once dedicate clinics started. Clinics were able to run safely through the pandemic, with direct access from the car park to the clinic, without need to use corridors or lifts.